Network properties of the global waste trade - Filippos K. Zisopoulos; Brian D. Fath; Xin Tong; Martin de Jong (Environmental and Sustainability Indicators)
The network properties of the global waste trade were assessed by using time series data of material and monetary flows between 2000 and 2022 from the online experimental database of Chatham House. More specifically, indicators from ecological network analysis and ascendency analysis were used to identity patterns which may not otherwise be directly identifiable, and to compare the network properties of the global waste trade to those of natural ecosystems. Focus was given on the distribution of monetary and material flows, on policy recommendations, and on future research avenues which we think are relevant for obtaining a more comprehensive understanding of socio-economic systems such as trade networks. This work provides a solid example of the application of network-based methods as an eco-mimicry approach for assessing the sustainability and fragility of socio-economic systems which can be of relevance to researchers and policy makers interested on transitions towards regenerative circular economies.